Penerapan Sistem Informasi Accurate Versi 5 terhadap Penyusunan Laporan Keuangan (Studi Kasus Pada CV Percetakan Karya) - Riyadi, Muhammad Azhar; Rouf, Abdul (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
Such rapid development in the business world, especially for SMEs, will greatly JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 JIAKES Jurnal Ilmiah Akuntansi Kesatuan Vol. 7 No 2 , 2019 pg. 246 - STIE Kesatuan ISSN 2337 – 7852 strengthen competitiveness between the scale of the company. The business development must be a concern for business owners to improve the quality of their business. The company must process the data resulting from its business operations into valuable information for quick and accurate decision making, in order to know how the business development is able to compete or not with its competitors. Information technology is said to help SMEs in providing the infrastructure needed to provide the right information for their users. The purpose of this research is to see how accurate program help business owners in preparing financial statements. This type of research is a qualitative descriptive type by conducting observations and interviews directly to CV Percetakan Karya. The result of this study shows that the accurate program can make easier to compile CV Percetakan Karya financial statements, the resulting report in the form of income statement and balance sheet report. The accurate program also makes easier fo CV Percetakan Karya to entry transaction data into the accurate program. The accurate program can provide detailed and complete financial statements, so companies can easily analyze the financial statements.